Faktor-faktor yang Mempengaruhi Keikutsertaan Pekerja Mandiri pada Program JKN di Poli Rawat Jalan - Indriati Indriati; Mugi Hartoyo; Sri Widiyati (Jurnal LINK, 2015)
This research is a quantitative study with a cross-sectional design, employing logistic regression methods. The number of sample of this study was 50 independent workers, determined by purposive sampling (judgmental sampling). The results of this research show that 54% respondents are not participants JKN. 56% of respondents have high knowledge, 56% high income, 88% high acceptability, and 54% negative attitude. The results also show that knowledge, attitude and income influence the JKN participation (p value 0.005, 0.000, and 0.000). Acceptability does not affect the JKN participation (p value 0.119). Knowledge is the dominant factor affecting the JKN participation with Exp (B) 5.94. In conclusion, people with high knowledge have 5.94 times higher chance for participants for JKN than people with low knowledge. It can be suggested that BPJS need to improve the knowledge of independent employee about JKN program using information dissemination.